INTEROPERABLE GOVERNANCE UNDER CONDITIONS OF DIGITAL TRANSFORMATION AND CRISIS CONSTRAINTS - Kurnosenko, Larysa (Public Management and Policy, 2026)
The article examines interoperability as a fundamental principle of public governance under conditions of digital transformation and crisis constraints. The deepening of European integration processes drives the relevance of the topic, the growing complexity of governance interactions, and the need to ensure institutional resilience of the state amid wartime and socio-economic challenges. The purpose of the study is to provide a theoretical substantiation of interoperable governance as an integral architecture of public authority coordination and to determine the prospects for developing an adaptive-combined model for Ukraine. The research employs systemic, institutional, and comparative approaches, as well as methods of conceptual analysis, structural-functional modeling, and content analysis of regulatory documents of the European Union and Ukraine. The multidimensional structure of interoperability is revealed, encompassing political, legal, organizational, semantic, and technical levels of interaction. National interoperability frameworks of EU countries are analyzed and typologized into centralized, decentralized, transitional, and point-to-point interaction models. It is substantiated that the choice of architectural model determines the parameters of institutional resilience, governability, and resource efficiency. The current state of interoperability development in Ukraine is assessed, particularly in the fields of digital services, healthcare, and public finance, and the regulatory preconditions for its institutionalization are examined. An adaptive-combined model of interoperable governance is proposed, combining a centralized coordination contour with decentralized management of sectoral registries. The conclusions demonstrate that interoperability functions not merely as a technological instrument but as a strategic principle of organizing public authority, capable of enhancing policy coherence, reducing governance losses, and strengthening state resilience under conditions of crisis complexity. Further research should focus on developing methodologies for assessing interoperability as an indicator of governance quality and institutional maturity of public authorities.